Managing Private Labels Based on Psychographic Consumer Segments: Emerging European Market Perspective - Horvat, Sandra; Ozretić Došen, Đurđana (Organizations and Markets in Emerging Economies, 2020)
This paper explores private labels in the context of Croatia, as a representative of a CEE and EU member countries, where their importance is continuously growing. It aims to reveal whether consumers’ psychographic characteristics impact their attitudes towards private labels, which are in the growth stage of the product life cycle. Findings show that price consciousness, consumer innovativeness, and store loyalty have a positive and statistically significant impact on consumers’ attitudes towards private labels. These three psychographic characteristics allow clustering of consumers prone to private labels (by applying K-means analysis) into three different clusters. Consumers belonging to cluster 2 exhibit the highest levels of innovativeness and price sensitivity and might be considered pioneers in accepting private labels. The paper contributes to a more comprehensive insight into private labels marketing management and offers managerial implications for retailers.
Keywords: private labels; psychographic characteristics; growth stage; product life cycle; emerging market